Anterior Cruciate Ligament Reconstruction Basics: Quadriceps Tendon (All-Soft Tissue) Autograft Preparation—Part 2 - Daniel J. Stokes, M.D.; Bryant P. Elrick, M.D., M.Sc.; Tyler R. Cram, D.O.; Katrina Schantz, P.A.-C.; Kevin K. Shinsako, P.A.-C.; Rachel M. Frank, M.D. (Arthroscopy Techniques)
Anterior cruciate ligament reconstruction with quadriceps tendon autograft is a reliable graft option that has recently increased in use. Varying harvesting and graft preparation techniques available and improved technology and implant design continue to make quadricep tendon preparation more efficient and reproducible. In this Technical Note, we describe our preferred technique for all-soft tissue quadriceps tendon autograft preparation after harvest for anterior cruciate ligament reconstruction.